Network pharmacology-based prediction of active compounds in the Wenyang Jiedu Huayu formula acting on acute-on-chronic liver failure with experimental support in vitro and in vivo - Tang, Dan; Wang, Ruo-Yu; Sun, Ke-Wei; Wu, Yunan; Ding, Lin; Mo, Yang (Frontiers in Pharmacology, 2022)
Acute-on-chronic liver failure (ACLF) is characterized by undermined liver function, massive necrosis/apoptosis of hepatocytes, and hepatic inflammatory cell recruitment, leading to multiorgan failure. Traditional Chinese medicine (TCM) has been widely applied in clinical and experimental studies of ACLF. In this study, 23 compounds with 6,386 drug targets were obtained from Wenyang Jiedu Huayu (WYJDHY), and 8,096 genes were identified as ACLF disease targets, among which 3,132 were overlapping co-targets. Expression profile analysis identified 105 DEGs among the co-targets, which were associated with biological activities such as lymphocyte activation, immune response regulation, and pathways such as Th17 cell differentiation and NF-κB signaling. After PPI analysis and network construction, atractylenolide I (AT-1) has been identified as the hub active ingredient of the WYJDHY formula. LPS stimulation inhibited rat hepatocytes’ BRL 3A cell viability, promoted cell apoptosis, increased the levels of ALT, AST, IL-6, and VCAM-1 within the culture medium, and activated NF-κB signaling, whereas AT-1 treatment significantly attenuated LPS-induced toxicity on BRL 3A cells. Furthermore, the NF-κB signaling inhibitor PDTC exerted effects on LPS-stimulated BRL 3A cells similar to those of AT-1, and the combination of PDTC and AT-1 further attenuated LPS-induced toxicity on BRL 3A cells. In vivo, AT-1 alone or with PDTC improved the symptoms and local inflammation in ACLF model rats. In conclusion, 23 active ingredients of six herbs in the WYJDHY formula were retrieved, and 105 co-targets were differentially expressed in ACLF. AT-1 exerts protective effects on LPS-stimulated hepatocytes and ACLF rats, possibly by inhibiting the NF-κB pathway.